2017
DOI: 10.1016/j.ahj.2017.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Increasing propensity to pursue operative closure of atrial septal defects following changes in the instructions for use of the Amplatzer Septal Occluder device: An observational study using data from the Pediatric Health Information Systems database

Abstract: Objectives Study trends in the treatment of atrial septal defects (ASD). Background Concern for device erosion following transcatheter treatment of ASD (TC-ASD) led in 2012 to a US FDA panel review and changes in the instructions for use (IFU) of the Amplatzer Septal Occluder (ASO) device. No studies have assessed the effect of these changes on real-world practice. Methods A retrospective observational study was performed using data from the Pediatric Health Information Systems Database of all patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Data about surgical cases, which would provide a more comprehensive view of practice in closing ASD and PDA, are not included in IMPACT®. A previous study has demonstrated that in a contemporary cohort of ASD’s treated at primary pediatric hospitals there is significant inter-hospital variability in the propensity to pursue operative or transcatheter closure of ASD after adjusting for measurable covariates 27 . Though it is conjecture, we would propose that this is also likely true for PDA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data about surgical cases, which would provide a more comprehensive view of practice in closing ASD and PDA, are not included in IMPACT®. A previous study has demonstrated that in a contemporary cohort of ASD’s treated at primary pediatric hospitals there is significant inter-hospital variability in the propensity to pursue operative or transcatheter closure of ASD after adjusting for measurable covariates 27 . Though it is conjecture, we would propose that this is also likely true for PDA.…”
Section: Discussionmentioning
confidence: 99%
“…Subjects of all ages who underwent transcatheter closure of an isolated ASD or PDA recorded in IMPACT ® between January 1, 2011 and September 30, 2015 were included in the study. Cases from hospitals with >15% incomplete data, contributing data for less than 6 months or at which less than 10 total ASD or PDA procedures were performed over the study period were excluded from analysis as described previously 21,27 . Individual cases were excluded if the ASD or PDA was not treated.…”
Section: Methodsmentioning
confidence: 99%
“…In analysis of data from the PHIS database, TC-ASD accounted for >80% of ASD closure procedures at US pediatric hospitals[9]. However, there was significant variation in how individual centers chose to pursue ASD closure with the range of ASD closure performed in the catheterization laboratory between 30 and nearly 100%[9]. Even after adjusting for differences in case-mix, there remained significant inter-hospital variability in the choice between O-ASD and TC-ASD[9].…”
Section: Practice Variation In Tc-asd Vs O-asdmentioning
confidence: 99%
“…TC-ASD with the current generation of devices has favorable rates of technical success and risk of adverse events when compared to operative closure of ASD (O-ASD)[38]. TC-ASD is the dominant technique for closing ASD; >80% of isolated ASD treated at primary pediatric hospitals in the United States are closed in the catheterization laboratory[9]. Though new devices continue to be developed, the technique for TC-ASD has remained essentially unchanged since the introduction of the Amplatzer Septal Occluder (ASO) in the early 2000’s.…”
Section: Introductionmentioning
confidence: 99%
“…ASO is a double-disc, self-expandable, occlusion device, which is made of nickel-titanium-alloy and approved for percutaneous closure of secundum ASD by the US Food and Drug Administration in 2001. [9][10] However, the efficacy of ASO on ASD in animal such as beagles remains to be determined. The molecular architecture of ASD involves down-regulated genes related to heart atrial septum formation, cardiomyocyte proliferation, and normal electrical conduction and muscle contraction, such as HERG, Mink, Kir2.1, Kir2.3, 11 CX40 (Connexin 40) and CX43 genes.…”
Section: Introductionmentioning
confidence: 99%